Capital of Commercial Banks and Mechanisms of its Management - Baxtiyorovich, Qahorov Bobur (European Journal of Life Safety and Stability (2660-9630), 2022)
In the article, the elements of capital of commercial banks, regulatory requirements for their adequacy are revealed based on econometric analysis. The state of capital of commercial banks is analyzed and practical proposals are made to improve the efficiency of income-generating assets.